A realist conception of truth - Alston, William P. 1921-2009 (Cornell Univ. Press, 1996)
One of the most important Anglo-American philosophers of our time here joins the current philosophical debate about the nature of truth with a work likely to claim a place at the very center of the contemporary philosophical literature on the subject. William P. Alston formulates and defends a realist conception of truth, which he calls alethic realism (from "aletheia," Greek for "truth"). This idea holds that the truth value of a statement (belief or proposition) depends on whether what the statement is about is as the statement says it is. Although this concept may seem quite obvious, Alston says, many thinkers hold views incompatible with it - and much of his book is devoted to a powerful critique of those views. Michael Dummett and Hilary Putnam are two of the prominent and widely influential contemporary philosophers whose anti-realist ideas he attacks